Model capturing the phenomenon of Durotaxis and showing higher rate of contractility stabilization is sufficient to capture the phenomenon. - Amrit Bagchi (20536044) (2025)
(a) Schematic of one-dimensional model showing direction of increasing substrate stiffness (ks) from left-to-right, discussed further in supplementary section. Simulated kymographs for (b) velocity, (c) traction and (d) strain-rate for durotaxis stiffness range of 0.06 nN/μm < ks < 12.3 nN/μm. Simulated kymographs for (e) velocity, (f) traction and (g) strain-rate for uniformly stiff substrates (ks = 12.3 nN/μm). Simulated kymographs for (h) velocity, (i) traction and (j) strain-rate for uniformly soft substrates (ks = 0.06 nN/μm). Plot showing different spatial variation of substrate stiffness (ks(xs)) used for testing the durotaxis model (k). Plot showing shift in center of mass of the cell mesh migrating on substrate mesh having different variations in ks(xs) (shown in plot k) (l).